18O, 2H, and ³H isotopic data for understanding groundwater recharge and circulation systems in crystalline rocks terrain of Southeastern Brazil. (June 2022) - Oliveira, Matheus S.M.; Neves, Mirna A.; Caxito, Fabrício A.; Moreira, Rubens M.
Abstract: The 18 O, 2 H and ³H isotopes have been used to identify recharge and circulation patterns in aquifer systems by determining the relationships between isotopic signatures of meteoric, ground, and surface waters. This research investigates a Crystalline Aquifer System in Southeastern Brazil, where the isotopic fractionation results from the effects of precipitation, altitude, and continentality, while the Local Meteoric Water Line (LMWL) is expressed as δ 2 H = 8.49 δ 18 O + 18.97. The isotopic signature of groundwater follows that of rain, varying according to the climate conditions of each sector of the basin. The groundwater in the upper sector of the basin have a renewal time of up to 25.75 years and low mineralization, being an important recharge zone for the Crystalline Aquifer System. However, in the lower and hotter sector of the basin, the evaporative processes influence the recharge and, therefore, the groundwater is more mineralized with a renewal time of up to 85 years, indicating an infiltrated water source upstream. Surface water is enriched with heavy isotopes resulting from evaporation due to sun exposure, with isotopic data plotting above the LMWL during the rainy season and similar to groundwater during the dry season, showing the effluent character of the main drainage channels. We propose a conceptual model where the isotopic signature and mineralization of groundwater are influenced by the relief, climate conditions, and lithological diversity. Highlights: Crystalline terrain relief controls the stable isotope signature of rainwater and groundwater. Crystalline terrain relief locally controls evaporative processes of recharge water. Groundwater recharge in hard rock terrains has local- and long-distance sources.